2011
DOI: 10.5009/gnl.2011.5.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, Depression and Quality of Life in Patients with Irritable Bowel Syndrome

Abstract: Anxiety and depression were frequently observed in Korean IBS patients and were related to the severity of their symptoms and the impairment of the patient's QOL. Our data suggest that assessing anxiety and depression is important when evaluating IBS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
95
1
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(133 citation statements)
references
References 43 publications
20
95
1
5
Order By: Relevance
“…In this study, the prevalence of CES-D 16 depression among individuals with IBS was 32.8%. The prevalence of CES-D 16 depression in our study was within the range of previous results (16-39%) (2,9,23,24). After adjustment for confounders, “active solution” coping behaviors were significantly associated with somatic symptoms.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, the prevalence of CES-D 16 depression among individuals with IBS was 32.8%. The prevalence of CES-D 16 depression in our study was within the range of previous results (16-39%) (2,9,23,24). After adjustment for confounders, “active solution” coping behaviors were significantly associated with somatic symptoms.…”
Section: Discussionsupporting
confidence: 89%
“…Regardless of etiology, IBS patients have heightened anxiety and depression scores, compared to healthy controls [11][12][13][14], as well as a significantly lower quality of life [11,15,16]. Lack of reliable diagnostic tests for IBS, combined with the patients' anxiety and stress induced by symptom variability, could lead to increased health care seeking [17,18], consequently exposing patients to numerous invasive, unpleasant and often unnecessary tests.…”
Section: Introduction/backgroundmentioning
confidence: 99%
“…[10][11][12][13][15][16][17][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] The baseline characteristics of included studies are shown in Table 1 22,29 Sphere score in 1 study, 24 and the Beck Anxiety Inventory (BAI) in 1 study. 30 …”
Section: Baseline Characteristics Of Included Studiesmentioning
confidence: 99%
“…A total of six studies were included. 15,17,18,37,38,65 In those studies, healthy-control groups were used for multiple comparisons with the three IBS-subtypes; we divided the healthy-control group into three groups for meta-analysis of three IBS-subtypes alongside healthy controls. Depression levels were significantly higher in IBS-C (SMD = 0.83; 95% CI, 0.61-1.06; I 2 = 0%; P < 0.001), IBS-D (SMD = 0.73; 95% CI, 0.51-0.96; I 2 = 0%; P < 0.001), and IBS with mixed bowel habits (SMD = 0.62; 95% CI, 0.39-0.84; I 2 = 0%; P < 0.001) (Fig.…”
Section: Depression and Anxiety In Irritable Bowel Syndrome-subtypementioning
confidence: 99%